Sex Differences in Suicide-Related Symptoms in a Large Military Sample. (2nd January 2017) - Rogers, Megan L.; Ringer, Fallon B.; Michaels, Matthew S.; Chiurliza, Bruno; Hagan, Christopher R.; Chu, Carol; Schneider, Matthew E.; Lim, Ingrid C.; Joiner, Thomas E.
ABSTRACT: Little research has focused on suicide-related symptoms in female servicemembers, despite high rates of suicidal behaviors. This study examined sex differences in suicide-related risk factors in 3, 374 U.S. Army Recruiters (91.9% male). Female servicemembers had a greater number of past major depressive and suicidal ideation episodes than did male servicemembers; there were no differences in suicide attempt histories or mental health visits. Female servicemembers reported significantly fewer symptoms of current suicidal ideation, perceived burdensomeness, and acquired capability. No significant sex differences emerged for thwarted belongingness, insomnia, or agitation. Our findings provide evidence for sex differences in rates of suicide-related symptoms among military personnel.